1993
DOI: 10.1007/bf01419673
|View full text |Cite
|
Sign up to set email alerts
|

The significance of here- and-now disclosure in promoting cohesion in group psychotherapy

Abstract: Here and now disclosure was compared to there-and-then

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 21 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…Yalom and Leszcz (2005) suggested that openly sharing one's inner experiences of other group members (immediacy), and having those experiences accepted by others, builds group cohesion. In addition, prior research (Slavin, 1993) has indicated that here-and-now intragroup communication (i.e., immediacy) predicted group cohesion. Given that interpersonal difficulties in using immediacy are often cited by trainees, it seems worthwhile to examine how immediacy training affects the perceived helpfulness of lab group climate.…”
Section: Outcomes Of Training Students To Use Immediacymentioning
confidence: 96%
“…Yalom and Leszcz (2005) suggested that openly sharing one's inner experiences of other group members (immediacy), and having those experiences accepted by others, builds group cohesion. In addition, prior research (Slavin, 1993) has indicated that here-and-now intragroup communication (i.e., immediacy) predicted group cohesion. Given that interpersonal difficulties in using immediacy are often cited by trainees, it seems worthwhile to examine how immediacy training affects the perceived helpfulness of lab group climate.…”
Section: Outcomes Of Training Students To Use Immediacymentioning
confidence: 96%
“…(1,3,16) In group session, the more therapist offers multiple relationships for assisting the individual growth in 'here-and-now', the more accomplishment in group therapy will become. (23) According to Yalom's theory, the group member acts as the power cell of the group. During therapeutic process, the therapist focuses on interaction and 'here-and-now' techniques to assist the member developing his/her interpersonal relationships.…”
Section: Background/ Objectives and Goalmentioning
confidence: 99%
“…In the group process, therapist will help the members to apply general information in order to their personal feelings or issues by shifting from personal feeling to interpersonal feeling or issue. (3,(23)(24)(25)(26) Second, the illumination of 'here-and-now' technique is the recognition of one's own behavior by understanding of one's behaviors may negatively affect others. Therapist will then advised 216 Long-term Group and Premature Drop out Groups in Psychotherapy: Yalom's 'Here and Now' Techniques the individual to practice more appropriate and positive behavior in order to avoid negative impacts to others.…”
Section: Background/ Objectives and Goalmentioning
confidence: 99%
See 1 more Smart Citation
“…Yalom's interpersonal group psychotherapy (also called interactive group psychotherapy), for example, stresses the "here-andnow" of the group's interaction over the analysis of events and experiences that occur outside of the group (the "then-andthere"; Slavin, 1993). Yalom's interpersonal group psychotherapy (also called interactive group psychotherapy), for example, stresses the "here-andnow" of the group's interaction over the analysis of events and experiences that occur outside of the group (the "then-andthere"; Slavin, 1993).…”
Section: Interpersonal Group Psychotherapymentioning
confidence: 99%